A study of perception and satisfaction on secondary school student with school learning facilities in SMK Datuk Bahaman / Mohamad Syahrul Nizam Rahmad - Rahmad, Mohamad Syahrul Nizam (2013)
This study was about a study of perception and satisfaction of secondary school student with school facilities in Sekolah Menengah Kebangsaan Datuk Bahaman. In this study, the researcher was used convenience sampling technique. Convenience sampling means a non-probability sampling procedure whereas the selected samples represent a captive audience. Non-probability sampling is the probability of selecting a single individual is not known, Salkind (2012). For the purpose of data collection, a questionnaire was used as the main instrument. The questionnaires consist of three sections including the demographic and two more sections were constructed according to Research Objective and Research Questions. 60 questionnaires have been distributed to SMK Datuk Bahaman. Several follow up and call were made to ensure that the researchers get back all the questionnaires. Within seven days, all the questionnaires were collected. Study result will be used to find a solution to facilities that provided in school. This research can make many of advantage in education sector in Malaysia. The data analysis was done by using SPSS 20.0. Survey instrument was conducted in the form of questionnaires and Likert scale observation will begin each analyzed the data obtained. Samples obtained through the research method Convenience Sampling of randomly selected samples or coincidence. The important of this research is that it gives a clear picture of student perception and satisfaction in their school. For the recommendation, the government and the school administrative should go forward to make sure the facilities can be in great condition to the student on future. In addition, for the future research, this research can be done in an urban area to make a clear comparison in facilities.